A Digital Approach to Retrofitting a Post and Core Restoration to an Existing Crown. Issue 7 (30th November 2017) - Lee, Ju‐Hyoung
Abstract: One problem that may arise in full‐coverage restorations is clinical crown fracture. Fracture of an endodontically treated and crowned tooth in the esthetic zone may be embarrassing to both the patient and clinician. If a completely sound margin and at least 2 mm of coronal structure remain, a fractured tooth may possibly be retreated by a repair. Several methods have been introduced to reproduce the original contour of the tooth for retrofitting an existing crown. If an existing crown is used as a template, excessive core material may remain over the margin, as loading the proper amount of core material is difficult, and making vent holes on the existing crown is not feasible. This article presents a repair technique to reuse an existing crown with computer‐aided design and computer‐aided manufacturing (CAD/CAM) technology. By using a milled poly(methylmethacrylate) matrix, the mentioned limitations are eliminated, and the original contour of the tooth can be effectively restored with minimal intervention. As an existing crown is reused, the issues of additional time and cost for repreparation, reimpression, and new crown are eliminated.